2006
DOI: 10.1080/02688690601046678
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary apoplexy: retrospective review of 30 patients—is surgical intervention always necessary?

Abstract: The objective of this article is to review clinical outcomes in patients presenting with pituitary apoplexy and compare the results of conservative and surgical management. It took the form of a retrospective review of 30 patients (23M, 7F; age range: 17-86 years) with pituitary apoplexy diagnosed between 1988 and 2004. Presenting features included headache in 27 patients, 'collapse' in three and vomiting in 14. Complete blindness occurred in four patients, monocular blindness in two, decreased visual acuity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
105
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 15 publications
3
105
2
4
Order By: Relevance
“…3,8,13,16,31 However, more recent series have repeatedly reported good outcomes in selected patients treated conservatively with medical therapy only. 5,9,13,17,21,23,25,31 In our study, 70% of the patients were treated with early resection, but the rest were treated with a delayed, planned surgical intervention (9%) or solely with medical treatment (21%). Treatment outcomes were similarly favorable with all treatment approaches.…”
Section: Discussionmentioning
confidence: 60%
“…3,8,13,16,31 However, more recent series have repeatedly reported good outcomes in selected patients treated conservatively with medical therapy only. 5,9,13,17,21,23,25,31 In our study, 70% of the patients were treated with early resection, but the rest were treated with a delayed, planned surgical intervention (9%) or solely with medical treatment (21%). Treatment outcomes were similarly favorable with all treatment approaches.…”
Section: Discussionmentioning
confidence: 60%
“…Several reports showed that spontaneous neurological recovery is possible, and some authors reported that patients treated conservatively had neurological and neuro-ophthalmological recovery rates similar to those of patients treated surgically (9). Other more recent retrospective studies have also provided evidence that nonsurgical treatment of patients with pituitary tumor apoplexy may be safe for patients who do not present visual deficits or show early evidence of recuperation from this condition (10,11). On the other hand, results of trans-sphenoid decompression immediately after stabilization of the patient have been very good, and recovery of neurological and pituitary function occurs within a period of several hours to days.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect it is noteworthy that many patients with pituitary apoplexy can be managed successfully with conservative, nonsurgical therapy with the same general success with long-term tumor control as occurs in surgical patients. 3,17,37 It should also be noted that this approach, if successful, would provide the potential of a tumoricidal treatment of these tumors, rather than the tumor-stabilizing effect of current medical therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The typical clinical entity was described relatively late, in 1950, by Brougham et al 12 Since then pituitary apoplexy has been the subject of many reports describing the clinical presentation, patient management, imaging features, and outcome, as well as reports of acute circumstances predisposing to its occurrence. 9,10,14,15,17,[22][23][24][25]29,32,36,37,39,45 We propose here that infarction of these tumors is the product of a combination of intrinsic features of these tumors and that it is the tenuous imbalance between their high rate of demand for nutrients combined with their limited intrinsic blood supply that makes them vulnerable to infarction, with or without precipitating events, and suggest that this circumstance may permit new approaches to treatment based on this peculiar vulnerability. …”
mentioning
confidence: 87%